Pendampingan Pembentukan Badan Usaha Milik Desa di Desa Tinting Boyok, Sekadau, Kalimantan Barat - Kristianus Nova; Arwanto Arwanto (Civitas Consecratio: Journal of Community Service and Empowerment, 2021)
The formation of village-owned enterprises is one of the efforts taken by all village officials to increase income and is expected to increase village economic growth. Village development through the establishment of facilities and markets is an effort to improve a strong economy. Based on field observations, it is shown that Village Owned Enterprises (BUMdes) are indispensable in Tinting Boyok Village considering the Village Original Income (PADes) is zero. The establishment of BUMDes aims to obtain additional funds where these funds can be used to help finance the development and economy of Tinting Boyok Village, considering that Tinting Boyok Village is still qualified as an underdeveloped village. The method used in this activity is analyzing village potential, socialization and coordination and grup discussion. There are several stages within this activity such as potential mapping activities, BUMDes socialization and mentoring. This activity intends to encourage the village government to increase village original income through the establishment and good governance of BUMDes in order to increase development in Tinting Boyok Village. This BUMDes is engaged in managing the sale and purchase of palm oil harvests in the village environment of Tinting Boyok Village. This is because Tinting Boyok village is a center for buying and selling palm oil crops in Sekadau Regency.